Information technologies and economic development in Latin America - Chong, Alberto 1963-; Yáñez-Pagans, Mónica ca. 20./21. Jh (Anthem Press, 2020)
Information Technologies in Latin America' provides a collection of rigorous empirical studies that contributes to a better understanding of the role and impact of old and new information technologies on Latin American economic development. It provides evidence using randomized and quasi-experimental designed studies for different information and communication technologies interventions. In evaluating their development impact a critical concern has been to contribute to the little existing evidence. In fact, whereas many ICT projects in the developing world have been promoted by multilateral organizations, bilateral aid agencies and nongovernmental organizations in recent years, the extent to which these interventions and policies actually contribute to the development of the region is unclear. The book provides evidence on what works and what does not